PELATIHAN PENERAPAN MODUL AJAR BERBASIS STEM-PJBL UNTUK MELATIH ENGINEERING DESIGN PROCESS SISWA SMA - Albertus Djoko Lesmono; Nila Mutia Dewi; Rif’ati Dina Handayani; Kendid Mahmudi; Bambang Supriadi; Niswatul Kariimah; Chilwatun Nasiroh (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
21st-century education that equips students with 6C skills is a crucial competency that students need to possess in order to compete in the global era. One effective learning approach for training these skills is STEM-Project-Based Learning (STEM-PjBL). Training and community service were conducted at SMAN Plus Sukowono to enhance teachers' competence in implementing STEM-PjBL-based teaching modules through structured training. The activity was conducted using a Community-Based Research (CBR) approach and involved 40 teachers as participants. The activity consisted of four stages: preparation, planning, implementation, and evaluation. The training included an explanation of the basic concepts of STEM-PjBL, an explanation of the teaching modules, and a simulation of the practical learning process of creating the “Da Vinci Bridge” project. The evaluation was conducted through a post-test consisting of 10 questions using Quizizz. The post-test results showed that most participants had a high level of understanding, with the majority of answers being accurate to within 90% or more of the correct answer. However, there was an important finding regarding the gap in understanding, where 80% of participants achieved perfect understanding, while the other 20% still needed reinforcement, especially in terms of conceptual foundations.These findings indicate that the training was effective in improving teachers' understanding of the STEM-PjBL teaching module, although follow-up is still needed to ensure equal competency. This activity is expected to strengthen the implementation of STEM learning in schools and support the development of students' 6C and EDP skills.